Circulatory System Diseases And Issues In Their Classification (Texas Journal of Engineering and Technology, 2025)
The circulatory system plays a critical role in maintaining the homeostasis of the body and ensuring general health, as it delivers nutrients, oxygen, and hormones to all parts of the body. However, various diseases that disrupt this complex system significantly affect individual well-being and public health. Conditions such as heart disease, hypertension, and vascular diseases are among the leading causes of morbidity and mortality worldwide. Despite their importance, the classification of circulatory system diseases remains a complex issue in the medical field